2018
DOI: 10.3892/mmr.2018.9093
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Letinous�edodes foot peptides against ethanol‑induced liver injury in L02 cells

Abstract: The aim of the present study was to evaluate the protective effect and mechanism of Letinous edodes foot peptides on ethanol‑induced L02 cells. A cell model of ethanol‑induced damage was established in vitro to study the effects of the Letinous edodes foot peptides on human L02 hepatocytes. The expression and activity of superoxide dismutase (SOD), malondialdehyde (MDA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alcohol dehydrogenase (ADH) and acetaldehyde dehydrogenase (ALDH), followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The above events eventually lead to increased ALT, AST, and ALP levels in the blood (Kazemi et al, 2017;Cengiz et al, 2019). Ma et al (2018) investigated the improving effect of lentinan on ethanol-induced L-02 cells. The findings indicated that anthocyanins had a significant impact on reducing ALT and AST activities induced by ethanol, thereby demonstrating a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…The above events eventually lead to increased ALT, AST, and ALP levels in the blood (Kazemi et al, 2017;Cengiz et al, 2019). Ma et al (2018) investigated the improving effect of lentinan on ethanol-induced L-02 cells. The findings indicated that anthocyanins had a significant impact on reducing ALT and AST activities induced by ethanol, thereby demonstrating a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…12 For example, mushroom foot peptides could alleviate alcohol toxicity through the activation of ADH and facilitation of alcohol metabolism. 13 Additionally, peptides in the hydrolysate of crucian carp swim bladder, could restore hepatic ADH activity and subsequently enhance the alcohol metabolism capacity in mice. 14 Our previous research observed that intracellular extracts of Lactococcus lactis (L. lactis) induced by ethanol increased ADH activity and improved alcohol metabolism in mice, suggesting that BAPs presented in stress-related proteins might play a relevant role.…”
Section: Introductionmentioning
confidence: 99%
“…BAPs with beneficial health effects can be generated via in vitro or in vivo digestion, including peptides with antioxidants, anti-inflammatory, ADH-activating, and hepatoprotective effects . For example, mushroom foot peptides could alleviate alcohol toxicity through the activation of ADH and facilitation of alcohol metabolism . Additionally, peptides in the hydrolysate of crucian carp swim bladder, could restore hepatic ADH activity and subsequently enhance the alcohol metabolism capacity in mice .…”
Section: Introductionmentioning
confidence: 99%